Carbon nanotube-supported Pt-Alloyed metal anode catalysts for methanol and ethanol oxidation - S. Themsirimongkon (2018)
© 2018 Hydrogen Energy Publications LLC To improve the electrocatalytic activity of alcohol oxidation, functionalized carbon nanotubes (CNTs) decorated with various compositions of metal alloy catalyst nanoparticles (PtxMy, where M = Au and Pd; x and y = 1–3) have been prepared via reduction. The CNTs were treated with an nitric acid solution to promote the oxygen-containing functional groups and further load the metal nanoparticles. X-ray diffraction (XRD) scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to probe the formation of catalyst microstructure morphologies. A uniform dispersion of the spherical metal particles with diameters of 2–6 nm was acquired. The catalytic properties of the catalyst for oxidation were thoroughly studied by electrochemical methods that involved in the cyclic voltammetry (CV), linear sweep voltammetry (LSV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). To maximize the electrocatalytic performance and minimize the metal integration of the loaded CNTs, various compositions of active catalysts with large active surface areas are expected to increase the activity of the enhanced catalysts for alcohol oxidation. Most of the prepared bimetallic catalysts have better alcohol oxidation kinetics than commercial PtRu/C. Among the prepared catalysts, the PtAu/CNTs and PtPd/CNTs catalysts with high electrochemically active surface area (ECSA) show excellent activities for alcohol oxidation resulting in their low onset potentials, small charge transfer resistances and high peak current densities and If/Ibratios, stability, and better tolerance to CO for alcohol oxidation. The integration of Pt and different metal species with different stoichiometric ratios in the CNTs support affects the electrochemical active surface area achieved in the catalytic oxidation reactions.